The Moderating Role of Knowledge Management on the Relationship between Information Technology and Total Quality Management: The Case of the Public Hospitals in Saudi Arabia - Al Ghamdi, Abdulrahman Ahmad; Abd Aziz, Fadzli Shah; Yusoff, Rushami Zien; Mustafa, Munauwar; Al-Matari, Ebrahim Mohammed (Medwell Journals, 2017)
The current study aims to examine relationship between information technology and total quality management in the public healthcare sector in Saudi Arabia. Moreover, the moderating effect of the moderating effect of knowledge management on the relationship between information technology and total quality management. The research design of the current study is quantitative using random sampling methods to choose respondents. In the data collection process 259 questionnaires were distributed among the respondents, while 165 questionnaires were received. Out of 165 questionnaire only 154 were found useful for further analysis. The results of the analysis showed that there is direct relationship exist between information technology and total quality management but knowledge management does not moderate the relationship between information technology and total quality management.